Pengaruh Customer Experience, Kemudahan Penggunaan, Promosi, Trust Terhadap Kepuasan Pelanggan Layanan Fitur GrabBike di Kota Samarinda - Aksenta, Almasari; Syachrul; Dewi, Tya Eka (Cattleya Darmaya Fortuna, 2024)
The rapid development of the internet has made things easier for people, including long-distance communication. The motorcycle taxi business that provides transportation services using motorbikes is growing along with technological advances. Grab is one of the application-based companies that makes it easy for consumers to get online motorcycle taxi services. This study aims to determine the effect of customer experience, ease of use, promotion, trust on customer satisfaction of the GrabBike feature service in Samarinda city. This study uses a quantitative approach using SPSS Version 26. The sample used was 100 respondents using lemeshow with a population of GrabBike feature service users in Samarinda City. The data analysis techniques used were instrument testing, multiple linear regression analysis, classical assumption testing, t-test, F-test and coefficient of determination. The results of this study indicate that partially customer experience does not have a significant effect on customer satisfaction. Ease of use, promotion, trust have a significant effect on customer satisfaction. The variables customer experience, ease of use, promotion, trust have a simultaneous effect on customer satisfaction.